RHETORIC OF MASCULINE SIGNS IN ADVERTISMENT “LUCKY STRIKE SEEING THINGS DIFFERENTLY” 2017 - Damar Tri Afrianto; Galih Putra Pamungkas (JURNAL PAKARENA, 2021)
The connotative advertising of advertising is certainly not sufficient to be interpreted conventionally, because each type of advertisement has its own character. Ads that try to convey implicit messages and communication about identity politics with rhetorical variants appear in the 2017 “Lucky Strike Seeing Things Differently” ad. it displays the daily routine rhetoric of a grown man with quite sublimative cinematic visuals. Today's rhetoric routine is very dominant with the practice of masculinity. The selected visual signs have an awareness of the masculinity of adult men, so that the audience is carried away by the practices of masculinity that are uniquely presented with daily relativity. The presentation of the sign of masculinity is important for research to reveal how the rhetoric of the sign in the advertisement “Lucky Strike Seeing Things Differently”. This research method uses Charles Sander Pierce's semiotic method which is related to the representative, object, and interpretant. The results of this analysis provide an understanding that this advertisement also tries to shape the perception of masculinity through the daily routine of men who become advertisements. The sign of masculinity is also directed at the physique inherent in the advertising model in the form of a tall, stocky, and long-haired posture.